Hoffmann Photograph MS608_3_2_002 - Canell (My University, 2013)
Black and white headshot of Hoffmann

Photographer's stamp: "Credit Requested Canell 112 W. 46 St. N.Y.C."
Keywords: Hoffmann, Gertrude